Poznoantično orožje na Slovenskem - Sivec, Irena (Arheološki vestnik, 1997)
The article is a brief historical review of the late Roman military history of Slovenia. The nucleus of the article is a review of the late Roman weaponry and military equipment from Slovenia. Certain questions are addressed, such as the continuity of military stations, their existence in the Migration period, the co-existence of military and civil inhabitants (particularly in urban centers, such as Emona), and the identification of the sites of production centers for military equipment and weapons.